Outcomes of 68Ga-NODAGA-Exendin-4 PET/CT Guided Surgical Management of Insulinomas in MEN1: A Preliminary Study - Ambulkar, Ketki Sunil; Shah, Ravikumar; Lila, Anurag; Sharma, Anima; Barnabas, Rohit; Karlekar, Manjiri; Memon, Saba Samad; Sarathi, Vijaya; Rege, Sameer; Verma, Priyanka; Malhotra, Gaurav; Lele, Vikram; Bandgar, Tushar (Nuklearmedizin - NuclearMedicine, 2025)
The data on the use of 68Ga-NODAGA-exendin-4 PET/CT in localizing multiple endocrine neoplasia type 1 (MEN1)-related insulinomas is evolving; however, surgical outcomes data are not available. We describe our cohort of patients with MEN1-related endogenous hyperinsulinemic hypoglycemia (EHH), where 68Ga-NODAGA-exendin-4 PET/CT was used to guide conservative surgery. A retrospective record review of MEN1-related EHH cases managed between 2000 and 2024 was performed for clinical features, imaging, and management. Outcomes were assessed for patients whose surgical extent was determined by 68Ga-NODAGA-exendin-4 PET/CT versus conventional imaging (CECT and 68Ga-DOTATATE PET/CT). Five patients with a median age of 17 (15.5–18.5 years) with EHH underwent laparoscopic, single lesion enucleation based on 68Ga-NODAGA-exendin-4 PET/CT. On preoperative imaging, CT identified culprit lesion in four, while 68Ga-DOTATATE PET/CT localized in one, and had one false positive uptake in non-functioning NET. The median duration of hospital stay was 6 (5.5–9) days. Over a median follow-up of 48 (3.5–84.5) months, none had EHH recurrence or exocrine/endocrine pancreatic insufficiency. On follow-up, one patient had an uneventful pregnancy and delivery. In the remaining 15, who underwent surgery based on conventional imaging, 12 (80 %) required extensive surgery beyond enucleation, of which two needed intraoperative ultrasound localization. This group had a postoperative hospital stay of 11 (8–23) days, one recurrence after 84 months, and pancreatic insufficiency in 5 (33 %). Our center observation suggests that GLP1R-based PET/CT-guided conservative insulinoma surgery in MEN1 patients is effective and safe and needs further validation.
Keywords: MEN1; exendin; GLP1; surgical outcomes; insulinoma; endogenous hyperinsulinemic hypoglycemia